Nursing interventions for urinary incontinence and sexual dysfunction after radical prostatectomy. - Gontijo Gomes, Cassia Regina; Appoloni Eduardo, Aline Helena; Mosteiro-Diaz, María-Pilar; Pérez-Paniagua, Javier; Alves Napoleão, Anamaria (Acta Paulista de Enfermagem, 2019)
Objective: Investigate, in the literature, nursing interventions to promote urinary continence and adapt to sexual dysfunction after radical prostatectomy. Methods: Integrative literature review in the databases PubMed, Web of Science, Scopus, CINAHL, and LILACS, using the descriptors "nursing care", "urinary incontinence", "erectile dysfunction", and "prostatectomy", and the keywords "nurse", "male sexual impotence" and "radical prostatectomy". Results: Eighteen publications were included, eight of which described interventions for urinary incontinence, five for sexual dysfunction and five for both complications. Three intervention strategies were found: 16 interventions for incontinence and 12 for sexual dysfunction. Conclusion: In the implementation strategies of interventions, the importance of nurses using different resources to attend to patients was observed. For urinary incontinence, the focus of interventions varied among educational, behavioral and physical. For sexual dysfunction, a predominance of psychoeducational actions was observed, involving the patients and, when possible the sexual partners.